PENERAPAN METODE SILABA UNTUK MENINGKATKAN KETERAMPILAN MENULIS PERMULAAN PADA MATA PELAJARAN BAHASA INDONESIA - Rinja Efendi (JURNAL PENDIDIKAN ROKANIA, 2017)
The purpose of this study to determine whether the through application of syllable method can improve students’ beginning writing skills of class IA at StateElementary School District 183 Pekanbaru on Indonesian subject. The observation of the first cycle of 1 st and 2 encounters are as follows: teachers’ activities 25 % and 75 %, students’ activities 71.79 %, and 78.84 %, students’ writing skills 66.66 % and 79.48 %. The result observations of the second cycle 1st and 2nd encounters are as follows: the activity of teachers 75 % and 100 %, students’ activities 87.17 % and 90.38 %, students' writing skills 87.17 % and 100 %. Based on the above results it can be concluded the application of syllable method can improve students’ writing skills in the class 1A of State Elementary 183 Pekanbaru .